2015
DOI: 10.17848/wp15-239
|View full text |Cite
|
Sign up to set email alerts
|

The Pros and Cons of Sick Pay Schemes: Testing for Contagious Presenteeism and Shirking Behavior

Abstract: This paper proposes a test for the existence and degree of contagious presenteeism and negative externalities in sickness insurance schemes. First, we theoretically decompose moral hazard into shirking and contagious presenteeism behavior and derive testable conditions. Then, we implement the test exploiting German sick pay reforms and administrative industry-level data on certified sick leave by diagnoses. The labor supply adjustment for contagious diseases is significantly smaller than for noncontagious dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…A simulation study found that having employees infected with influenza stay home and out of the workplace could reduce influenza transmission in the workplace by 25–40%, and providing PSL would reduce workplace infections by 6% [34]. Another study reported that the spread of ILI decreased by about 5% after some U.S. cities mandated worker access to PSL benefits [35]. A recent study also found that children of parent with PSL benefits were more likely to receive flu vaccination [36].…”
Section: Discussionmentioning
confidence: 99%
“…A simulation study found that having employees infected with influenza stay home and out of the workplace could reduce influenza transmission in the workplace by 25–40%, and providing PSL would reduce workplace infections by 6% [34]. Another study reported that the spread of ILI decreased by about 5% after some U.S. cities mandated worker access to PSL benefits [35]. A recent study also found that children of parent with PSL benefits were more likely to receive flu vaccination [36].…”
Section: Discussionmentioning
confidence: 99%
“…Presenteeism is also important in that it goes along with several undesirable side effects. It is not just that sick workers are usually less productive 1 , going to work when ill may also spread infectious diseases to co-workers (see, e.g., Pichler and Ziebarth, 2015), exacerbate individuals' bad health status, and result in long-term health problems (as shown by Hansen and Andersen, 2009). Some observers (like Hemp, 2004) thus argue that presenteeism is even more costly and harmful than absenteeism, i.e.…”
Section: Motivationmentioning
confidence: 99%
“…This provides stronger evidence that some of increase in absenteeism may be arising due workers abusing 23 A smaller strand of the literature examines presenteeism -the act of attending work while sick -more explicitly. See, for example, Pichler and Ziebarth (2015), Markussen, Mykletun, and Røed (2012), and Dew, Keefe, and Small (2005).…”
Section: Augmenting This Data With Google Flu Trends Allows Us To Idementioning
confidence: 99%